The photoprotective and collagen stimulatory effects of labisia pumila var pumila extract on UVB irradiated human skin fibroblast (HSF1184) cells - Mohd. Hanafi@Hanafiah, Mohd. Mukrish (2012)
This study mainly concentrates on the investigation of the photoprotective effect of Labisia pumila extract on the growth of Human Skin Fibroblasts cells (HSF1184) and collagen synthesis by the HSF1184 cells. In this study, the water extract of Labisia pumila and the methanolic extract of Labisia pumila showed growth stimulatory effect on HSF1184 cell line at the same concentration throughout the study, at 1x 10-5 µg/ml. At higher concentrations, both Labisia pumila plant extracts showed inhibitory effect on the growth of the cells, after 24 hours of treatment. After 48 hours of treatment, all concentrations of the water extract of Labisia pumila showed growth stimulatory effect on the HSF1184 cells in both nonultraviolets B (UVB) irradiated and UVB irradiated cells cultured in media with fetal bovine serum (FBS) or without FBS. The growth stimulatory effect was more significant in HSF1184 cells culture media without FBS. These results demonstrate the time dependent effect of the water extract of Labisia pumila on the HSF1184 cells. Both plant extracts caused significant increase in the collagen production of the HSF1184 cells in both UVB and non UVB irradiated HSF1184 cells. At concentration of 1 x 10-5 µg/ml, the water extract of Labisia pumila was able to increase the collagen synthesis in the HSF1184 UVB irradiated cells up to 70% whereas the methanolic extract of Labisia pumila has increased the collagen synthesis only by 20%, this concentration has proven to be the optimum concentration for both extracts of Labisia pumila throughout the course of this study and this result clearly indicate that the water extract of Labisia pumila is a better extract than the methanolic extract of Labisia pumila. In conclusion, the Labisia pumila plant extracts showed a significant photoprotective effect and has great potential to be developed and integrated into cosmeceutical product in the future.